Red blood cell membrane omega-3 fatty acid levels and physical performance: Cross-sectional data from the MAPT study. Issue 4 (August 2018) - ,; Vellas, Bruno; Guyonnet, Sophie; Carrié, Isabelle; Brigitte, Lauréane; Faisant, Catherine; Lala, Françoise; Delrieu, Julien; Villars, Hélène; Combrouze, Emeline; Badufle, Carole; Zueras, Audrey; et al.
Summary: Background & aims: Studies have shown that omega-3 polyunsaturated fatty acids (PUFAs) are associated with brain, cardiovascular and immune function, as well as physical performance and bone health in older adults. So far, few studies have highlighted the associations between PUFA status and performance-based tests of physical function. To study the associations between the omega-3 index (red blood cell (RBC) membrane content of omega-3 PUFAs, such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)) and physical performance measured with the Short Physical Performance Battery (SPPB) in a sample of community-dwelling older adults. Design: Cross-sectional study using the baseline data of the Multidomain Alzheimer's Disease Trial (MAPT), a randomized, placebo-controlled trial. Participants and measurements: 1449 participants with available data on PUFAs were included. Omega-3 index and Short Physical Performance Battery (SPPB) scores were measured at enrollment and the omega-3 index expressed as the percentage of total fatty acid content was calculated. We also dichotomized the omega-3 index as low (lowest quartile) vs. high (three upper quartiles). Results: Participants were 75.2 (±4.4) years old, 64.5% were female. Bivariate analyses found that participants who were in the lowest omega-3 index quartile (Q1) had a SPPB score significantly lower than participants in the three other quartiles (Q2–Q4). However, adjusted (for age, gender, cognitive function, depressive status, Body Mass Index and grip strength) multiple linear regression showed that the omega-3 index-SPPB score association did not reach statistical significance [β = −0.166; (−0.346; 0.013); p = 0.07] in our sample. Conclusion: This cross-sectional study found that participants with a low omega-3 index had worse performance-based test results of physical function than people with a high omega-3 index, but this association did not reach statistical significance once confounders were controlled for. Studies looking at the over-time associations between PUFA status and physical performance changes may shed more light on this topic.